2008
DOI: 10.1007/s00401-008-0351-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of A5 noradrenergic neurons in multiple system atrophy

Abstract: The A5 noradrenergic group of the pons projects on the medulla and spinal cord and contributes to control of sympathetic activity and respiration. Because these functions are affected in multiple system atrophy (MSA), we sought to determine whether there was involvement of A5 neurons in this disorder. We counted tyrosine-hydroxylase (TH) immunoreactive neurons in the A5 area and locus ceruleus in the pons obtained from six patients with clinical and neuropathological diagnoses of MSA and six age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…These results appear to reflect the neuronal loss in the LC of MSA patients, which has been demonstrated in neuropathological studies [3,27]. Therefore, distinguishing MSA patients from normal subjects and PD patients can be done plausibly based on selective involvement of LC in neuromelanin MRI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results appear to reflect the neuronal loss in the LC of MSA patients, which has been demonstrated in neuropathological studies [3,27]. Therefore, distinguishing MSA patients from normal subjects and PD patients can be done plausibly based on selective involvement of LC in neuromelanin MRI.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, Kashihara et al [18] reported that reduced volume of neuromelanin-positive SNc was found in patients with MSA using neuromelanin imaging based on the signal decrease of SNc compared with that of surrounding brain tissue. However, no report in the relevant literature has described neuromelanin imaging regarding the LC in MSA, although MSA patients exhibit autonomic symptoms and neuronal loss and gliosis in the SNc and LC (more predominantly in the latter) [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have evidenced that severe loss of A5 neurons in the A5 area contributes to the manifestation of autonomic disorder associated with the neurodegenerative disease of multiple system atrophy (Benarroch et al, 2008). These observations open the possibility that changes in the functioning of A5 neurons may underpin the development of augmented sympathetic levels, especially in pathological conditions associated with hyperactivity of peripheral chemoreceptors, such as obstructive sleep apnea (Narkiewicz et al, 1998), heart failure (Toledo et al, 2017) and neurogenic hypertension (Pijacka et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, central chemoreception was thought to be exquisitely localized to the ventral surface of the medulla in the classic L, S, and M regions in cats and rats [16]. Subsequent research with different paradigms indicate, however, that many sites within the brainstem respond to focal acidification in vivo and many types of neurons respond to CO 2 /pH in vitro [6, 7, 10, 15, 16, 18, 24, 25, 28, 3032, 39, 40]. These regions include the LC [7, 32], nucleus of the solitary tract [30, 32], caudal and rostral raphé [25, 39], retrotrapezoid nucleus [10, 15, 16, 25], preBötzinger complex [40], and fastigial nucleus of the cerebellum [28].…”
Section: Discussionmentioning
confidence: 99%
“…An underpopulation of TH-neurons is also suggested in A5 as well as the LC in our case. This bilateral site in the ventrolateral tegmentum of the caudal pons is comprised of TH-neurons involved in sympathetic tone and the modulation of respiratory-related neurons, in part via projections to chemosensitive populations on the ventral medullary surface [6]. …”
Section: Discussionmentioning
confidence: 99%